Electronic Online Handwriting Character Recognition System Using Arduino Platform - Ahmad Radzi, Syafeeza; Ngan, Albert Ban Chew; Mohd Sadari, Muhammad Muhaimin Hilmi; Kamaruddin, Mohamad Nasriq; Wong, Jia Li; Md Zauber, Zarini (Penerbit UTM Press, 2017)
This paper proposes an online prototype approach of handwriting character recognition system using a microcontroller. The main contribution of this work is the simple method of translating a handwriting input from analog to a digital font using XOR bit-wise operation. This system recognizes characters and numbers in natural handwriting with a stylus. This electronic system is used to improve the technology from the use of a bulky keyboard system to a portable and convenient way which is more suitable for smaller electronic devices nowadays such as smart phone, tablet and etc. In order to construct the system, a Arduino Mega is used as the microcontroller along with the Arduino TFT Touch Shield and an LCD screen as the input and output respectively as the hardware components. For the software part, this system uses C language and Arduino software (IDE). The recognition result achieved is 80.0%.